Environmental impact on surface marine sediments from industrial and urban liquid waste - Cabrera Carranza, Carlos (2004)
Descriptions of environmental impact are necessary to predict the effects of specific projects on defined and often small areas, as is the case of the bay of Chancay. In this bay residual water from the fish industry and urban spilling are usually discharged. Environmental impact caused on marine sediments is deduced from an evaluation of the bio-oceanographic conditions this bay presents. Impacts generated this way vary according the environmental variables sensitivity or fragility, thus it is, for example, that impact on whichever of them can put the rest of the trophic chain in danger.Such is the case of this research, environmental impact is produced on the short-run and takes place when fishing industrial processing plants are working. The one on the long-run takes place due to the gathering of residues and pollutants that can become irreversible or unavoidable as time goes. The impacts evaluation and identification processes were made through interaction matrixes of causeeffect, which allows us to identify and quantify the characteristics of those impacts causing the spillings of the Bay of Chancays shallow sediments in a systematic way. We can conclude that environmental impacts are associated with addition of organic materials in all its forms, originating from the various effluents, even though they are not essentially made up of substances or compounds considered to be toxic or dangerous. The whole addition of organic charge, by the various liquid effluents or from the fishing industrial activity and urban spilling, calculated in 36,851.53 TMB DBO5/year, make changes on water and sediments quality, reaching up to 0.00 ml/L of 02, 100mg/L of DBO5 and 0.00 bits/ind., turning into a severe impact because of the effects on the research area ecosystem and landscape.